The Genetic Basis of Phenotypic Heterogeneity in the Neuronal Ceroid Lipofuscinoses - Gardner, Emily; Mole, Sara E. (Frontiers in Neurology, 2021)
The neuronal ceroid lipofuscinoses (NCLs) are a group of inherited neurodegenerative disorders that affect children and adults. They share some similar clinical features and the accumulation of autofluorescent storage material. Since the discovery of the first causative genes, more than 530 mutations have been identified across 13 genes in cases diagnosed with NCL. These genes encode a variety of proteins whose functions have not been fully defined; most are lysosomal enzymes, or transmembrane proteins of the lysosome or other organelles. Many mutations in these genes are associated with a typical NCL disease phenotype. However, increasing numbers of variant disease phenotypes are being described, affecting age of onset, severity or progression, and including some distinct clinical phenotypes. This data is collated by the NCL Mutation Database which allows analysis from many perspectives. This article will summarise and interpret current knowledge and understanding of their genetic basis and phenotypic heterogeneity.